2008
DOI: 10.1172/jci32020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-7 on memory CD8+ T cell homeostasis are influenced by the timing of therapy in mice

Abstract: IL-7 is integral to the generation and maintenance of CD8 + T cell memory, and insufficient IL-7 is believed to limit survival and the persistence of memory CD8 + T cells. Here, we show that during the mouse T cell response to lymphocytic choriomeningitis virus, IL-7 enhanced the number of memory CD8 + T cells when its administration was restricted to the contraction phase of the response. Likewise, IL-7 administration during the contraction phase of the mouse T cell response to vaccinia virus or a DNA vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 55 publications
2
75
0
Order By: Relevance
“…By using this model, we found that TS/A tumours expressing LACK as an intracellular tumour-associated Ag (TS/A-LACK tumour cells) promote the expansion of short-lived LACK-specific effector-like CD4 1 T cells, while hinder the accumulation of both natural-and vaccine-induced central memory-like T cells [10,15]. As IL-7 is known to support memory CD4 1 T-cell expansion following Ag withdrawal [41], we asked whether this cytokine could be used in short-term in vitro cultures for the expansion of tumoursensitized CD4 1 T cells useful in ACT settings. In agreement with our previous findings, CD4 1 CD44 high T cells able to bind I-A d /LACK fluorescent multimers (Fig.…”
Section: Il-7 Favors the Accumulation Of Tumour-sensitized Cd4 1 T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using this model, we found that TS/A tumours expressing LACK as an intracellular tumour-associated Ag (TS/A-LACK tumour cells) promote the expansion of short-lived LACK-specific effector-like CD4 1 T cells, while hinder the accumulation of both natural-and vaccine-induced central memory-like T cells [10,15]. As IL-7 is known to support memory CD4 1 T-cell expansion following Ag withdrawal [41], we asked whether this cytokine could be used in short-term in vitro cultures for the expansion of tumoursensitized CD4 1 T cells useful in ACT settings. In agreement with our previous findings, CD4 1 CD44 high T cells able to bind I-A d /LACK fluorescent multimers (Fig.…”
Section: Il-7 Favors the Accumulation Of Tumour-sensitized Cd4 1 T Cellsmentioning
confidence: 99%
“…In some cases IL-7 amplifies Agdriven T-cell responses [32][33][34][35][36], favors the transition of effector to memory cells [31,[37][38][39], and sustains a slow, homeostaticlike, Ag-independent memory T-cell proliferation [24,30,40]. Furthermore, its administration at the time of Ag withdrawal supports memory CD8 1 T-cell generation [41], and enhances vaccine-mediated immunity when provided in adjuvant settings [42,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rIL-7 treatment during the contraction phase of the T-cell response increased Ag-specific memory CD8 1 T-cell proliferation and improved their function in mice [6]. It was recently demonstrated that IL-7 in combination with anti-IL-7 mAb significantly increased homeostatic T-cell expansion compared to IL-7 alone [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to acute effector T cells, memory T cell populations are capable of prolonged persistence in the absence of antigenic stimulation through a process of homeostatic proliferation that is largely driven by in vivo exposure to IL-7 and IL-15 [20][21][22]. When melanoma tumors were inoculated into mice 60 days after LCMV infection, at which time remaining LCMV-specific T cells are of memory phenotype, populations of LCMV-specific memory T cells after 18 days of tumor growth (the same interval used in our previous experiments examining resting and acutely activated T cells) were no different than in tumor-free control mice.…”
Section: Discussionmentioning
confidence: 99%